The Relationship between Hotel Rating and Customer Outcomes and Its Implication towards Revisit Intention - Suresh Kumar; Miftah Zikri (President University, 2018)
This research aims to examine HOLSERV with three dimensions namely, employee, tangible andreliability, towards its relationship on customer satisfaction and return intention rather thanSERVQUAL because it suits hotel environment. The object analysis was Bandung which proclaimedherself as a tourism city with quiet number of hotels rating as non-star to five-star hotels. From 41three-star hotels, this research managed to cover 29 hotels to conduct this research. Respondents withtotal number of 355 participated to fill the questionnaire with the helped of hotel managers byspreading it to their customers who were checking out of the hotel. Structural equation modeling wasapplied to test the hypothesis and the results show that tangibility and reliability influence customers’satisfaction but not employee. In addition, customer satisfaction influences return intention.